Internal capital market mergers in weak external market environment: An emerging market evidence. (31st July 2019) - Huang, Wei; Zhang, Hong; Goyal, Abhinav; Laws, Jason
Abstract: Using Chinese split‐share structure reform as backdrop, we study the alternative theories explaining the change in objectives of internal capital markets (ICMs) after regulatory intervention. Focusing on related party merger and acquisitions, as the primary form of ICM transactions in China, we document significantly positive performance improvement among the acquiring firms around related party than nonrelated party merger and acquisitions in the period following the split‐share structure reform. This evidence is particularly stronger among acquirers with lower institutional shareholding. Our findings are invariant to the length of performance evaluation window, matched samples, model specifications, acquirers' ownership structure, and business group affiliations. After controlling for alternative channels of tunnelling and propping, contrary to the popular belief, our findings support the bright‐side view of ICMs postregulatory intervention in an emerging market set‐up.